Lung transplantation from controlled donation after circulatory death using simultaneous abdominal normothermic regional perfusion: A single center experience. Issue 7 (18th April 2022) - Mora, Victor; Ballesteros, Maria Angeles; Naranjo, Sara; Sánchez, Laura; Suberviola, Borja; Iturbe, David; Cimadevilla, Bonifacio; Tello, Sandra; Alvarez, Carlos; Miñambres, Eduardo
Abstract : Despite the benefits of abdominal normothermic regional perfusion (A‐NRP) for abdominal grafts in controlled donation after circulatory death (cDCD), there is limited information on the effect of A‐NRP on the quality of the cDCD lungs. We aimed to study the effect of A‐NRP in lungs obtained from cDCD and its impact on recipients´ outcomes. This is a study comparing outcomes of lung transplants (LT) from cDCD donors (September 2014 to December 2021) obtained using A‐NRP as the abdominal preservation method. As controls, all lung recipients transplanted from donors after brain death (DBD) were considered. The primary outcomes were lung recipient 3‐month, 1‐year, and 5‐year survival. A total of 269 LT were performed (60 cDCD and 209 DBD). There was no difference in survival at 3 months (98.3% cDCD vs. 93.7% DBD), 1 year (90.9% vs. 87.2%), and 5 years (68.7% vs. 69%). LT from the cDCD group had a higher rate of primary graft dysfunction grade 3 at 72 h (10% vs. 3.4%; p < .001). This is the largest experience ever reported with the use of A‐NRP combined with lung retrieval in cDCD donors. This combined method is safe for lung grafts presenting short‐term survival outcomes equivalent to those transplanted through DBD. Abstract : Transplantation of lungs procured in controlled donation after circulatory death with use of normothermic regional perfusion shows equivalent outcomes to transplantation of lungs procured in donation after brain death.